Life of Stefan Dečanski by Danilo’s Student and by Grigorij Camblak (Comparative Analysis) - Kostić Tmušić, Aleksandra S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The purpose of the article is to show how two authors, one Serbian and the other Bulgarian, saw the great Serbian ruler and how they composed his biography. Even though the authors were not contemporaries, their work exhibits similar pattern. However, they write in different styles, and their views and opinions differ. In this article, we will try, with a comparative method, to reliably present the life of Stefan Dečanski from the point of view of two great medieval writers.
Keywords: Danilo’s student; Grigorij Camblak; Stefan Dečanski; old Serbian literature; biography